Conceptualization of depressive disorders and their treatment in Positive and Transcultural Psychotherapy (Part 2) - Roman Ciesielski (The Global Psychotherapist)
In this article, the author attempts to conceptualize the treatment of depressive disorders through the lens of positive and transcultural psychotherapy (PPT), referring to the main tenets of this approach and his own experience as a psychotherapist and psychiatrist. The most important aspects are included here to structure and operationalize the psychotherapy of depression. Relational aspects and differential analysis of symptoms, psychodynamic conflicts, and early symptomatic experiences are discussed.